Pengaruh Promosi Flash Sale dan Website Quality terhadap Impulse Buying pada Marketplace Shopee : Studi pada Mahasiswa Pengguna Shopee di Bandar Lampung - Juwita, Tia Viany; Hartono, Hartono; Subagja, Ghia (Jurnal Bisnis dan Pemasaran Digital, 2022)
Purpose: This research was conducted with the aim of finding out the effect of flash sale promotions and website quality on the impulse buying of students using Shopee in Bandar Lampung. Research Methodology: The approach used is quantitative with explanatory research techniques. The type of data is primary data derived from questionnaires distributed via Google form to 385 respondents. In this study, sampling using purposive sampling technique. Variable measurement uses a Likert scale and is tested using SmartPLS v.3 with SEM (Structural Equation Model) as the analysis method. Results: This study resulted that partially flash sale promotion had a positive and significant effect of 65.8% on the impulse buying variable, and the website quality variable had a positive and significant effect of 19.1% on the impulse buying variable. Meanwhile, based on the test results together or simultaneously, it results that the flash sale promotion and website quality variables have a positive and significant effect of 66.4% on impulse buying. Limitations: In this study, there were only two endogenous variables, namely flash sales and website quality, and they only existed in the city of Bandar Lampung. Contribution: The results of this study reinforce previous research, where there is a positive effect between flash sales and website quality on impulsive purchases. so that it is expected to increase sales.